Unexpected Nucleophilic Substitution Reaction of BODIPY: Preparation of the BODIPY–TEMPO Triad Showing Radical‐Enhanced Intersystem Crossing. Issue 7 (15th February 2018) - Xu, Kejing; Sukhanov, Andrey A.; Zhao, Yingjie; Zhao, Jianzhang; Ji, Wei; Peng, Xiaojun; Escudero, Daniel; Jacquemin, Denis; Voronkova, Violeta K.
Abstract : We have discovered a new and unexpected substitution reaction of BODIPY. Through single‐crystal XRD analysis, DFT calculations, and other complimentary spectroscopic methods, we have confirmed that the molecular structural assignment of the previously reported nucleophilic substitution of the halogenated carbon atom at the meso position of BODIPY was inaccurate. Indeed, in these substitution reactions, the amino attaches to the methyl group at the 3‐ or 5‐position and not on the meso ‐carbon of the BODIPY core. As a result of this unexpected substitution reaction, we prepared a BODIPY dimer, attached to the stable radical TEMPO (2, 2, 6, 6‐tetramethyl‐1‐piperidinyloxyl). We confirmed the efficient formation of the triplet state ( Φ Δ = 59 %, τ T = 2.8 µs) of this BODIPY–TEMPO triad through the radical‐enhanced intersystem crossing mechanism by using nanosecond time‐resolved transient absorption spectroscopy. Through time‐resolved EPR spectroscopy, the doublet (spin angular momentum quantum number S = 1/2) and quartet ( S = 3/2) states of the triad were observed. Moreover, we observed a strong intramolecular ground‐state interaction between the BODIPY chromophores in the triad, which shows new spectral features different to those of H‐ or J‐aggregates and the exciton coupling effect. These TEMPO‐labeled compounds were used as triplet photosensitizers for triplet–triplet annihilation (TTA) upconversion (quantum yield Φ UC = 4.7 %). Abstract : We confirm that amino substitution occurs at the 3‐ or 5‐position of BODIPY and not at the previously reported meso position. We prepared the BODIPY–TEMPO triad, which shows efficient triplet state formation. Through time‐resolved EPR, excited doublet ( S = 1/2) and quartet ( S = 3/2) states were observed. Interaction between the BODIPY chromophores in the triad results in new spectral features.